2014
DOI: 10.3945/ajcn.113.076786
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-calibrated protein intake and bone health in the Women’s Health Initiative clinical trials and observational study

Abstract: Higher biomarker-calibrated protein intake within the range of usual intake was inversely associated with forearm fracture and was associated with better maintenance of total and hip BMDs. These data suggest higher protein intake is not detrimental to bone health in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 25 publications
(28 reference statements)
7
69
1
1
Order By: Relevance
“…Additional retrospective analyses using the UUN-to-urinary creatinine ratio and change in this ratio as surrogate markers of TPro also saw a similar lack of effect on changes in bone quantity. The WP results from the current study are in agreement with 2 previous WP supplementation trials (51,57), while the TPro results are inconsistent with results from prospective cohort studies (24)(25)(26) and a meta-analysis of randomized controlled trials showing a beneficial effect with increased TPro on bone quantity (27). Both Zhu et al (51) and Kerstetter et al (57) assessed the effects of WP supplementation on bone quantity and, similar to the current study, found neither a deleterious nor a beneficial effect.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additional retrospective analyses using the UUN-to-urinary creatinine ratio and change in this ratio as surrogate markers of TPro also saw a similar lack of effect on changes in bone quantity. The WP results from the current study are in agreement with 2 previous WP supplementation trials (51,57), while the TPro results are inconsistent with results from prospective cohort studies (24)(25)(26) and a meta-analysis of randomized controlled trials showing a beneficial effect with increased TPro on bone quantity (27). Both Zhu et al (51) and Kerstetter et al (57) assessed the effects of WP supplementation on bone quantity and, similar to the current study, found neither a deleterious nor a beneficial effect.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, the observed hypercalciuria effect of increasing protein intake is often explained by this enhanced calcium absorption, which subsequently does not alter total calcium balance (23). Despite dietary proteinÕs lack of effect on total calcium balance, prospective cohort studies have shown that higher TPro is associated with higher bone mineral density (BMD) (24)(25)(26). A 2009 metaanalysis of randomized controlled trials also supports this claim, showing a beneficial effect of higher TPro on spine BMD in adults (27).…”
mentioning
confidence: 55%
“…This result confirms previous cross‐sectional and prospective findings of a positive relationship between higher total protein intake and higher BMD in women 6, 7, 8, 9. We found no association between intake of vegetable protein and BMD, contradicting some previous studies,10, 11, 12 but we did observe a clear association between intake of vegetable protein and prevalence of low bone mass (osteoporosis or osteopenia).…”
Section: Discussionsupporting
confidence: 71%
“…A systematic review on the relationship between protein and bone health reported no adverse associations between protein intake and bone mineral density (BMD) and a meta‐analysis of six randomized controlled trials showed a beneficial effect of protein supplementation (40 mg of milk basic protein or 20.4 g total protein) on lumbar spine BMD of 0.02 g/cm 2 5. A number of cross‐sectional and prospective studies have also reported associations between higher total protein intake and higher BMD in women 6, 7, 8, 9. Data indicate that protein source (animal or vegetable) may influence the relationship between protein intake and bone health because protein from animal sources is high in acidic amino acids such as cysteine and methionine,3 although these acidic amino acids are also found in plant‐based sources such as nuts.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that skin collagen integrity is strictly entangled with protein malnutrition. Clinically, this has been proven by the impaired growth in malnourished children [22] and the importance of implementing an adequate protein intake in the elderly to maintain bone health [23].…”
Section: Skin Aging Collagen and The Effects Of Malnutritionmentioning
confidence: 99%